THE IMPACT OF VIRTUAL REALITY, BASED ON COLLABORATION AND COOPERATION, ON THE LEARNING AND EDUCATION OF YOUTH - Florentin Remus MOGONEA (Analele Universităţii din Craiova. Psihologie, Pedagogie)
The use of information and communication technology in education has shed new light on the very notion of learning, supporting the possibility of its achievement through online collaboration. In well-designed online learning environments, students experience meaningful knowledge acquisition in an e-Learning community, where collaborative group activities are encouraged. Together with the emergence of the knowledge society and the theory known as "connectivism", knowledge is transformed into a certain dynamic relationship model, and learning is transformed into a continuous process of new connections and creation of network patterns. Knowledge increasingly becomes a social act distributed through networks. Today, global connectivity facilitates new ways of social interaction and allows collaboration in virtual environments, turning students into protagonists of common actions. In recent decades, researchers have explored the extent to which information and communication technology could support the collaborative learning process. While some have relied on learning theories already developed without considering computer support, others have suggested that the field needs a theory adapted to the challenges faced by those trying to specifically understand how technology contributes to the achievement of collaborative learning. New developments in collaboration theory shows the fact that ICT offers new types of media, which encourage the collaborative construction of knowledge, facilitate the comparison of knowledge constructed by different groups and help groups in the act of negotiating the knowledge they build. Moreover, these technologies and models eliminate blockages in the communication process with the teacher (Albulescu, 2021).